Teknik reseksi mandibula pada autopsi - Tanjung, Rizki; Soedarsono, Nurtami; Yuniastuti, Mindya; Ibrahim Auerkari, Elza (Jurnal Kedokteran Gigi Terpadu, 2023)
Background: Jaw resection in the forensic autopsy has a different purpose rather than the usual goals such as removal of the tumor, fracture repair or reducing osteomyelitis. However, the purpose of forensic autopsies is actually to identify the remains of victims who cannot be identified with fingerprints or DNA conventionally or by means of identifying unidentified victims. Objective: This study aims to review jaw resection techniques at autopsy. Method: Scoping review is carried out by analyzing secondary data in the form of journals published from 2008-2021. Results: There were five journals used in this study. The five journals show that the jaw resection procedure starts from an incision first and then a cut is made to the maxilla or mandible. Conclusion: Jaw resection at autopsy is needed for sufficient visibility. It is usually reserved for cases of severely rotting or burned body parts.